Acoustic feedback and its control in the selection and use of hearing aids - Rama Mohan Babu P; Aruna Chitre (Journal of All India Institute of Speech and Hearing, 1973)
Acoustic Feedback is the whistling sound which results when a very quiet sound which comes from the receiver of a hearing aid is picked up by the microphone, amplified and putout, at the receiver again'. Dale (1962). Acoustic Feedback is a very common problem that is encountered wherever hearing aids are used. To prevent A.F.B. (Acoustic Feedback) the hearing aids are attached to earmoulds of various types like the Stock Ear pieces or the Moulded Ear Pieces. The former type of ear pieces are available in various sizes commercially. The earpiece is chosen so it approximately fits the ear of the user and as such it reduce the A.F.B. only to a little extent. Stock Ear Pieces are recommended only when the moulded ear pieces cannot be made available. Steps must be considered to reduce this Acoustic Feedback because not only is the resulting squeal unpleasant, it may also drown out the sounds that the wearer wishes to hear.